Pengaruh Self Efficacy dan Dukungan Sosial Terhadap Resiliensi Mahasiswa Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Sumatera Utara - Halimsyah Rambe, Ifrahunnada; Nuraini, Nuraini; Dewi, Salamiah Sari (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This associative quantitative research aims to determine the influence of self-efficacy and social support on the resilience of students at the State Islamic University of North Sumatra. Data collection was carried out through questionnaires and interviews, with analysis using multiple linear regression and coefficient of determination using SPSS 27. The research population was 177 students majoring in Madrasah Ibtidaiyah Teacher Education, and the sample used was 123 people using the Slovin method. The test results show that simultaneously, self-efficacy and social support influence resilience, with Fcount > Ftable (78.403 > 3.92). The partial test shows that self-efficacy (X1) has a significant effect on resilience (Y), with a value of tcount > ttable (10.695 > 1.657), while social support (X2) has no significant effect, because tcount < ttable (0.388 < 1.657). The significance value for self-efficacy < 0.05 and social support > 0.05. The results of the coefficient of determination test show that 56.6% of the variance in resilience can be explained by self-efficacy and social support, while 44.4% is explained by other factors not studied. Thus, self-efficacy has a significant positive effect on resilience, while social support does not show a significant effect